Characterization and anti-cancer effects of citral-loaded nanostructured lipid carrier in breast cancer cells in vitro and in vivo - Nordin, Noraini (2017)
Breast cancer is a life-threatening health issue in women globally. Metastasis has been attributed as a key factor for the increase in cancer-related deaths. Innovative research elucidatinga possible cure for cancer via inhibition of metastatic ability has received considerable interest. However, although various cancer therapeutic such as chemotherapy are useful, their unmanageable side effects still remain unresolved. To address this issue, cancer nanotherapy has been utilized to establish a novel drug delivery system for anticancer agents. Nanostructured lipid carrier is one of the systems that still under investigation due to its applicability. Citral (Cymbopogon citratus), a member of essential oil family is mainly derived from the extraction of lemongrass which is popular in pharmaceutical, food, perfume and cosmetic industries. Studies showed that citral has anti-proliferative properties on several cancers including breast cancer. Citral is a poor aqueous solubility compoundthat has been studied to inhibit cancer developments. In this study, it is postulated that the incorporation of citral into nanostrucuted lipid carrier (NLC) will improve solubility and delivery of the compound while not compromising its therapeutic effects. Thus, the objective of the current study is to characterize the formulation of nanostructured lipid carrier loaded with citral and to evaluate its anti-cancer effects in MDA MB-231 cells in vitro and on breast cancer cells 4T1 in murine mice model. Notably, citral was loaded into the NLC using high pressure homogenization methods. Characterization of NLC-citral was determined using Transmission Electron Microscope (TEM), zeta potential, drug loading and drug release studies. TEM and zeta sizer analyses revealed that NLC-citral is a nano size particle with an average diameter size of 54.12 ± 0.30 nm. Meanwhile, zeta potential of NLC-citral was -12.73 ± 0.34 mV with an entrapment efficiency of 98.9 ± 0.124%, and drug loading was 9.84 ± 0.041%. No mortality, toxic signs and changes of serum biochemical profile observed in the healthy mice after being exposed with NLC-citral for 28 days via oral administration.In addition, through flow cytometry cell cycle analysis, Annexin V analysis, JC-1 and fluorometric assays, it was shown that NLC-citral managed to induce G2/M arrest and induced apoptosis in MDA MB-231 cells. Besides, the percentage of cells in G2/M arrest also increased in NLC-citral in a concentration dependent manner. Furthermore, a prominent antimetastatic ability of NLC-citral was demonstrated in in vitro scratch, migration and invasion assays. A significant reduction of migrated and invaded cells was observed in the NLC-citral treated MDA MB-231 cells. To further evaluate apoptotic and antimetastatic mechanism of NLC-citral at the molecular level, microarray-based gene expression profiling and proteomic profiling were conducted. Based on the result obtained, NLC-citral was found to regulate several important signaling pathways related to cancer development such as apoptosis, cell cycle and metastasis signaling pathways. Results obtained from gene expression analysis were validated through the targeted RNA sequencing and real time polymerase chain reaction. Subsequently, this observation was testedin vivo in a murine model utilizing murine breast cancer 4T1 cells using BALB/c mice. Treatment using NLC-citral significantly led to a reduction of tumor size inthe treated mice. Outcomes of histopathology and TUNEL analyses showed that the number of cancer cells in the tumor decreased 28 days post oral treatment with NLC-citral (3.5-fold). Furthermore, proteomic profiling and real time polymerase chain reaction confirmed anti-tumor effects of NLC-citralin vivo. In conclusion, the NLC-citral system inhibited the proliferation of breast cancer cells in vitro and in vivo, majorly through the induction of apoptosis, reduction of inflammation, activation of anti-angiogenesis and anti-metastasis potential. This study shows that loading of citral into NLC did not alter the therapeutic potential of citral and the NLC-citral is a promising and effective anticancer agent for breast cancer therapeutics.The NLC thus has excellent potential to be developed into a drug-carrier and delivery system for the treatment of cancers.